1992
DOI: 10.1164/ajrccm/146.4.930
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacologic and Neurochemical Evidence for the Activation of Capsaicin-sensitive Sensory Nerves by Lipoxin A4in Guinea Pig Bronchus

Abstract: Exogenous administration of lipoxin A4 (LXA4) to guinea pig isolated bronchus produced contractile effects in a concentration-dependent manner (1, 3, and 6 microM). These responses were potentiated when preparations were previously incubated with thiorphan (10 microM), an inhibitor of tachykinin breakdown, but were significantly depressed when sensory nerves were previously desensitized in vitro by capsaicin (10 microM for 15 min) challenge. Ruthenium red (10 microM for 20 min), a blocker of the cationic chann… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

1993
1993
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 11 publications
0
11
0
Order By: Relevance
“…Cationic proteins were potent stimulators of sensory C-fibers, releasing -20% of CGRP-LI induced by capsaicin, which is similar to that induced by other mediators such as bradykinin (29), histamine (29,30), and lipoxin A4 (31). The kinetics of the release of CGRP between the two cationic proteins was different, however, in that poly-L-arginine induced a slowly developing, prolonged release of CGRP-LI, while poly-L-lysine induced a rapid and transient release.…”
Section: Discussionmentioning
confidence: 78%
“…Cationic proteins were potent stimulators of sensory C-fibers, releasing -20% of CGRP-LI induced by capsaicin, which is similar to that induced by other mediators such as bradykinin (29), histamine (29,30), and lipoxin A4 (31). The kinetics of the release of CGRP between the two cationic proteins was different, however, in that poly-L-arginine induced a slowly developing, prolonged release of CGRP-LI, while poly-L-lysine induced a rapid and transient release.…”
Section: Discussionmentioning
confidence: 78%
“…This substance is thus a potential candidate for the much sought after endogenous vanilloid receptor agonist ( Szallasi & Blumberg, 1999 ) that joins a growing list of endogenous activators/modulators of the vanilloid receptor, including inflammatory mediators ( Stucky et al ., 1998 ; Vyklicky et al ., 1998 ), hydrogen ions ( Caterina et al ., 1997 ; Vyklicky et al ., 1998 ), heat ( Caterina et al ., 1997 ; Tominaga et al ., 1998 ), arachidonic acid ( Manzini et al ,. 1989 ; Manzini & Meini, 1991 ), lipoxin A 4 ( Meini et al ., 1992 ), products of the lipoxygenase pathway ( Hwang et al ., 2000 ), and prostacylin ( Mapp et al ., 1991 ). In contrast, anandamide has recently been shown to inhibit the release of neuropeptides from sensory nerves in the rat via a CB 1 ‐dependent mechanism ( Richardson et al ., 1998a , 1998b ) indicating that anandamide may have both inhibitory and excitatory actions on sensory nerves.…”
Section: Introductionmentioning
confidence: 99%
“…Lipoxin was also the first lipidergic pro-resolvent to be studied in terms of an ion channel-associated action. In 1992, around which the curiosity regarding lipid-ion channel interaction was increasing due to the findings that some eicosanoids were shown to activate K + channels (Buttner et al, 1989; Kim and Clapham, 1989), lipoxin A4 was demonstrated to excite dorsal root ganglionic sensory neurons as measured by surrogate outputs of increased bronchus contraction and neuropeptide secretion (Meini et al, 1992). Blockage and desensitization of the vanilloid subtype transient receptor ion channel (TRPV1) each prevented this effect, although it was not electrophysiologically confirmed, implicating that TRPV1 activity may be enhanced by lipoxin A4 exposure.…”
Section: Fatty Acid-derived Pro-resolventsmentioning
confidence: 99%
“…Lipoxin A4 did not exhibit competitive binding with a TRPV1 agonist to the natural protein in the neuronal membrane. However, early binding assays were not perfectly reliable as it was later shown that TRPV1 protein was not actually used in this assay (Meini et al, 1992). Thus it remains elusive whether lipoxin A4 directly binds to this ion channel or indirectly modulates its activity via signal transduction events to exert this excitatory effect.…”
Section: Fatty Acid-derived Pro-resolventsmentioning
confidence: 99%